"stategi frugal innovation dalam digitalisasi pembelajaran PAI: analisis problematika dan kesenangan belajar di tengah keterbatasan infrasruktur". - Hilyatul ulya Halim; Saza Dwi Aulia; Muhammad Nuzli; Hilyatul ulya Halim; Saza Dwi Aulia; Muhammad Nuzli (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2026)
The digitalization of Islamic Religious Education learning in elementary schools is frequently constrained by technological infrastructure limitations, while prior studies have focused on the digital divide without examining teachers' adaptive strategies. This study aims to analyze the frugal innovation strategy adopted by teachers in implementing the digitalization of Islamic Religious Education learning at an elementary school facing limited facilities. The study employed a descriptive qualitative approach with a case study design at SD IT Raudhatul Ilmi, Jambi. Data were collected through in-depth interviews, participant observation, and documentation, and were subsequently analyzed using the interactive model of Miles, Huberman, and Saldana, which comprises data condensation, data display, and conclusion drawing. Data validity was strengthened through source and technique triangulation. The findings reveal that limited internet connectivity and inadequate devices cause a time inefficiency of approximately 10 to 15 minutes in each learning session due to restricted network coverage and the alternate use of devices. Through the frugal innovation strategy, teachers overcome these constraints by creatively utilizing available resources, particularly the collective use of audio-visual media through Smart TV and the support of teachers' personal resources. This strategy positively affects students' joyful learning, reflected in their enthusiasm and active participation. The novelty of this study lies in mapping frugal innovation as an adaptive framework for technology-based religious learning within a context of infrastructure limitations.